COVID‐19‐Related Knowledge, Protective Behaviors and the Moderating Role of Primary Sources of Information: Findings from a Cross‐Sectional Online Survey in the United States. (15th September 2021) - Kim, Sooyoung; Ali, Shahmir H.; Jones, Abbey; Capasso, Ariadna; Foreman, Joshua; DiClemente, Ralph Joseph; Tozan, Yesim
Abstract : Research Objective: To assess the moderating effects of primary sources of COVID‐19 information on the association between knowledge and protective behaviors against COVID‐19. Study Design: This is a secondary analysis of data from a cross‐sectional online COVID‐19 survey conducted among US adults in April 2020 using advertisement‐based recruitment on social media. A total of 6518 people completed the survey. Linear regression analysis was performed on COVID‐19 knowledge and protective behavior scores. An interaction term between knowledge and primary source of information was included in order to examine any moderating effects of the information source on the relationship between knowledge and protective behaviors. The analysis was adjusted for demographic and socio‐economic factors and was conducted using R software (version 3.6.3). Population Studied: Adult population (age > 18) living in the United States. Principal Findings: Overall, higher level of COVID‐19‐related knowledge was associated with higher level of self‐reported engagement in protective behaviors. More specifically, our results indicate that the primary source of information modified the association between knowledge and protective behaviors. The most effective sources of information to translate incremental knowledge into higher engagement in protective behaviors were interpersonal communication and social media. Official sources such US government, CDC, and WHO websites had significantly weaker effects. Our results also showed that respondents with lower knowledge scores preferred social media or interpersonal communication as their primary source for seeking COVID‐19‐related information. Conclusions: This study shows the important role that the different COVID‐19 information sources can play on influencing people's engagement in protective behaviors while delivering the COVID‐19‐related knowledge. Implications for Policy or Practice: Overflowing information and misinformation are influencing people's degree of engagement in protective behaviors against COVID‐19. Policy makers should carefully monitor the use of different information sources by the public so that they can effectively target, influence decision‐making, and promote behavior change to fight the current pandemic and the infodemic concurrently.